A Robust Control for Five-level Inverter Based on Integral Sliding Mode Control - Le, Thanh-Lam; Nguyen, Vinh-Quan (International Journal of Integrated Engineering, 2023)
This paper presents a new control strategy for cascaded H-bridge five-level inverter (CHB-5LI) based on the novel sliding mode control (NSMC). The proposed method can generate pulse-width modulation (PWM) without using conventional modulation techniques based on carrier waves. With the proposed NSMC technique, the PWM pulses can be obtained by the control signal u(t) from the output of the sliding mode controller and the levels of comparison. To eliminate the chattering and increase the speed convergence of the controller, the integral sliding-mode surface combined with a first-order low-pass filter (LPF) is used. The stability of the control system is validated by Lyapunov theory. The simulation and experimental results show that the proposed NSMC method has strong robustness, and better performance for multi-level inverter control systems with low total harmonic distortion, Common-Mode (CM) voltage reduction, switching frequency diminution, and less switching loss.